Structural, Morphological, Thermal and Mechanical Study of a Geopolymer Based on Metakaolin Mixed with Oujda Clay - Youssef Bachirat; Assaad Elouafi; Abdeslam Tizliouine (Engineering Proceedings)
This study investigated a metakaolin-based geopolymer blended with Oujda clay, replacing 5–15 wt% of metakaolin (MK) and is focused on structural, thermal stability, and microstructural changes in the geopolymer pre- and post-high temperature exposure, using XRD, TGA, FTIR, and SEM. Results showed that Oujda clay addition increased compressive strength to 33 MPa with 15 wt% clay after 28 days of curing. To facilitate the replacement of metakaolin-based geopolymer, the amount of metakaolin was decreased by incorporating Oujda clay. This strategy enabled chemical and mechanical properties comparable to those of traditional metakaolin-based geopolymer, while also introducing a more locally sourced and potentially cost-effective material.